Memanusiakan Manusia Melalui Pendidikan di Dalam Keluarga Menurut Pemikiran Driyarkara dan Ki Hajar Dewantara - Gaudensius Krisantus Sutanto (Fakultas Teologi, Universitas Sanata Dharma, 2025)
Article written by the author focuses on explaining about Driyarka and Ki Hajar Dewantara’s ideas and taught about education in the family. Ki Hajar Dewantara, put forward the concept of the Three Centers of Education, which states that education occurs in the family, school and social community, with the family as the first and main educational environment. His famous principle,